Video-based supervision for training of endoscopic submucosal dissection - Bhatt, Amit; Abe, Seiichiro; Kumaravel, Arthi; Parsi, Mansour A.; Stevens, Tyler; Jang, Sunguk; Lopez, Rocio; Oda, Ichiro; Vargo, John J.; Saito, Yutaka (Endoscopy, 2016)
Background and study aim: Adoption of endoscopic submucosal dissection (ESD) in Western countries has been limited by the difficulty in learning the procedure. Although a porcine model is commonly used for ESD training, without expert guidance the procedure is difficult to master. The availability of Western ESD experts is limited, and expert supervision through a remote video-based system may be a practical method for Western endoscopists to learn ESD. The aim of this study was to assess the value of video-based remote evaluation in supervising ESD training.Methods: Two Western endoscopists performed ESD training procedures in an ex vivo porcine model at least every 2 weeks until competency was achieved. Competency was defined as consistent en bloc resection of a 3-cm area within 30 minutes, and without perforation, using the proper ESD technique. A Japanese ESD expert at the National Cancer Center in Tokyo, Japan, analyzed the training videos, scored them, and provided written feedback for improvement after each training session and before the trainee’s next training session.Results: Endoscopist 1 reached competency at 23 procedures and endoscopist 2 reached competency at 25 procedures. No difference in skill improvement between the two endoscopists was noted. One trainee subsequently completed eight ESD procedures in patients, with curative en bloc resection and no complications.Conclusion: A standardized ESD training program including educational presentations/videos and preclinical animal training with expert guidance through a remote video-based system is an effective tool for learning ESD techniques in preparation for performing the procedure in humans.